Resolusi Konflik Berbasis Islam Nusantara: Model Peacebuilding Nahdlatul Ulama - Saiyidinal Firdaus (LAKPESDAM MWCNU Palengaan, 2026)
This study aims to develop an Islam Nusantara–based conflict resolution model through the peacebuilding practices of Nahdlatul Ulama (NU). Data were collected through document analysis, semi-structured interviews, and observation of mediation and community dialogue practices. The study involved 20 informants consisting of community leaders and mediators selected through purposive sampling. Data were analyzed using reflexive thematic analysis combined with a hybrid coding strategy (deductive–inductive), while research quality was maintained through trustworthiness procedures. The findings reveal that NU’s conflict resolution practices operate through four interconnected mechanisms: religious authority legitimacy, community dialogue, operationalization of Islam Nusantara values (tawassuṭ, tasāmuḥ, and tawāzun), and expansion of practices through cross-context transfer and adaptation. The synthesis of findings generates a conceptual model structured through the sequence of Islam Nusantara values, Nahdlatul Ulama institutional practices, social mediation, relational transformation, and peacebuilding. This study contributes to the development of religious peacebuilding and conflict transformation scholarship by integrating theological dimensions, social practices, and locally grounded peace mechanisms. Penelitian ini bertujuan mengembangkan model resolusi konflik berbasis Islam Nusantara melalui praktik peacebuilding Nahdlatul Ulama (NU). Data dikumpulkan melalui analisis dokumen, wawancara semi-terstruktur, dan observasi terhadap praktik mediasi dan dialog komunitas. Penelitian melibatkan 10 informan yang terdiri atas tokoh masyarakat dan mediator yang dipilih menggunakan purposive sampling. Analisis data dilakukan menggunakan reflexive thematic analysis dengan strategi hybrid coding (deduktif–induktif), sementara kualitas temuan dijaga melalui prinsip trustworthiness. Temuan penelitian menunjukkan bahwa praktik resolusi konflik NU dibangun melalui empat mekanisme utama, yaitu legitimasi otoritas keagamaan, dialog komunitas, operasionalisasi nilai Islam Nusantara (tawassuṭ, tasāmuḥ, dan tawāzun), serta ekspansi praktik melalui transfer dan adaptasi lintas konteks. Sintesis temuan menghasilkan model konseptual yang bergerak melalui alur nilai Islam Nusantara, praktik kelembagaan Nahdlatul Ulama, mediasi sosial, transformasi relasi, dan peacebuilding.